PEMBAGIAN BEBAN TURBIN GAS UNTUK EFISIENSI BAHAN BAKAR PADA PROSES PRODUKSI LISTRIK DI PT. INDONESIA POWER - Yuliani Puji Astuti, (Matematika dan Sains, 2011)
Since the need of electricity power is increased and the lack of fuel as basic production material, then the electrical power optimalization becomes critical thing. One of the alternative to increase production efficiency can be achieved by optimalizing production task that described on the load distribution which comes out in certain interval and time for each gas turbine as electrical production machine. Method that used in this paper is dynamic programming that fit with the multistages optimation. While to identify production system characteristic than Lagrange Polynomial Interpolation is used based on the production data.